2019
DOI: 10.1016/j.ijscr.2019.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of delayed presentation of intraperitoneal bladder rupture following caesarean delivery: A case report

Abstract: Highlights Bladder injury is an uncommon complication of cesarean delivery with an incidence ranging from 0.0016% to 0.94%. Delayed blabber rupture post CD may present with urinary ascites and elevated serum creatinine mimicking acute kidney injury. Cystography is the diagnostic imaging of choice with the reported accuracy of 85%–100%. Surgical repair is the treatment of choice for intraperitoneal bladder injury. Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Meanwhile, bladder ruptures are managed depending on their type, either being intraperitoneal with a 25% occurrence rate, or extraperitoneal with an occurrence of 60-65%) [ 4 ]. Aghaways et al previously reported a similar case of bladder injury that was managed with a Foley catheter and percutaneous intraperitoneal pigtail catheter and omitted the surgical intervention due to the instability of the patient [ 6 ]. Afterwards, the patient responded well to conservative management without the need for surgical intervention [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, bladder ruptures are managed depending on their type, either being intraperitoneal with a 25% occurrence rate, or extraperitoneal with an occurrence of 60-65%) [ 4 ]. Aghaways et al previously reported a similar case of bladder injury that was managed with a Foley catheter and percutaneous intraperitoneal pigtail catheter and omitted the surgical intervention due to the instability of the patient [ 6 ]. Afterwards, the patient responded well to conservative management without the need for surgical intervention [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aghaways et al previously reported a similar case of bladder injury that was managed with a Foley catheter and percutaneous intraperitoneal pigtail catheter and omitted the surgical intervention due to the instability of the patient [ 6 ]. Afterwards, the patient responded well to conservative management without the need for surgical intervention [ 6 ]. Furthermore, it has been documented in the literature that cases of uncomplicated EPBI due to pelvic fractures can be managed conservatively with a large-bore catheter for a three-week duration [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management protects patients from anaesthetic risks and surgical complications [ 6 ]. Nonoperative management of bladder perforation could either be in the form of insertion of an indwelling transurethral Foley catheter alone or a combination of bladder and peritoneal drainage [ 8 ]. Studies have shown that nonoperative treatment for intraperitoneal bladder rupture is appropriate if there is no associated organ injury that requires laparotomy and if there is availability of adequate bladder drainage and no complications such as peritonitis [ 4 , 14 ], all features that were achieved in this patient.…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of the bladder is an uncommon complication of EC that may have grave consequences if not diagnosed and treated early [4]. For smaller intraperitoneal bladder ruptures, recent reports have shown that a conservative approach may be sufficient if urinary antibiotic prophylaxis is continued after initial antibiotic therapy, and continued urinary drainage through an indwelling catheter is provided for a minimum of two weeks, until closure of the perforation is evident on the CT cystogram [5][6][7][8]. Similarly, certain international guidelines have recently adopted a conservative approach in the management of small, uncomplicated intraperitoneal bladder perforations [9].…”
Section: Introductionmentioning
confidence: 99%
“…The definitive treatment for intraperitoneal bladder rupture typically involves surgical repair [1]. However, conservative treatment with urinary drainage is an alternative management strategy associated with favorable outcomes without any complications [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%